The dielectrical and alternating current conductivity properties of 40Cu+20CO+40Y2O3 ceramic - Yakuphanoğlu, Fahrettin; Evin, Ertan; Okutan, Mustafa (Elsevier Science Bv, 2006)
Electrical and dielectrical properties of the 40Cu + 20Co + 40Y(2)O(3) ceramic have been investigated as a function of frequency and temperature. The results obtained indicate that CBH conductivity model is dominant in the conductivity mechanism of the ceramic. The electronic parameters such as density of the states at the Fermi level, N(E-F) and hopping distance, R, of the ceramic were calculated. The temperature dependence of AC conductivity shows two conduction regions, in which the rate of increase of the conductivity is different. The temperature-dependent AC conductivity of the ceramic exhibits an Arrhenius behavior. The temperature dependence of the dielectric constant at different constant frequencies is investigated and the dielectric constant increases linearly with increasing temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AC conductivity; CBH model; dielectric constant; ceramic